The Making of Democrats - Manning, C. author. aut Link
IX, 198 p. 3 illus.
Keywords: Can elections create democrats? Why and how do formerly armed opposition groups decide to invest in electoral politics or to undermine them? This book argues that the answer lies in the patterns of inter- and intraparty struggles created by participation in repeated elections over time.